ANALYSIS OF THE IMPLEMENTATION OF THE MAIN DUTIES AND FUNCTIONS OF THE SOCIAL SECURITY ADMINISTERING BODY (BPJS) FOR HEALTH IN BANDAR LAMPUNG CITY - Fellya Putri Irene; Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used is descriptive qualitative research. This method aims to describe the analysis of the implementation of the Social Health Security Agency's policy in Lampung Province. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that the implementation of the Social Health Security Agency's main duties and functions in Bandar Lampung City has, in principle, been carried out in accordance with applicable regulations for the administration of National Health Insurance. However, its effective implementation still faces various obstacles in the dimensions of communication, resources, implementer disposition, and bureaucratic structure. These obstacles impact the quality of service, public understanding, and coordination between stakeholders. Therefore, continuous improvement efforts are needed to optimally achieve policy objectives. Inhibiting Aspects: (a) Communication: There are still limitations in the clarity and consistency of policy information to the public and health facilities; (b) Resources: Limited number and competence of human resources; and suboptimal support for facilities and infrastructure; (c) Disposition or Attitude of